2003
DOI: 10.1081/ese-120016897
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Mercury from Clayey Soils Using Electrokinetics

Abstract: Numerous sites have been polluted with mercury as a result of accidental spills and improper disposal practices, and these mercury-contaminated sites may have adverse effects on human health and the environment. Innovative and cost-effective remediation techniques are urgently needed, and this study was performed to investigate the use of electrokinetics for mercury-contaminated soils. Initially, batch tests were performed on two soils, kaolin and glacial till, spiked with mercury(II) to investigate mercury de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…HgI 4 2− ions are readily mobile through contaminated soil and removed at the anode. Reddy et al (2003a) have identified potassium iodide (KI) as the best mercury complexing agent among many others for HgCl 2 removal using electrokinetic methods. Using 0.1 M KI, they obtained~97 % removal of spiked mercury (500 mg Hg 2+ kg −1 soil) in laboratory electrokinetic experiments.…”
Section: Electrokinetic Techniquesmentioning
confidence: 99%
“…HgI 4 2− ions are readily mobile through contaminated soil and removed at the anode. Reddy et al (2003a) have identified potassium iodide (KI) as the best mercury complexing agent among many others for HgCl 2 removal using electrokinetic methods. Using 0.1 M KI, they obtained~97 % removal of spiked mercury (500 mg Hg 2+ kg −1 soil) in laboratory electrokinetic experiments.…”
Section: Electrokinetic Techniquesmentioning
confidence: 99%
“…Zheng Shenshen adopted the method of cathode electric supplemented by cation exchange membrane and KI + I 2 solution oxidation complex method to remediate mercury contamination typical paddy soil in Guizhou and the Hg removal efficiency can reach 68.6% [33] . Reddy made the removal efficiency of mercury in the soil increase to 97% by adding 0.1 mol/L KI to kaolin [34] . Cox added I 2 /KI lixiviant in cathode and made the insoluble Hg into Hgl 4 complex anion, so that the mercury removal efficiency was as high as 99% [35] .…”
Section: A Electrokinetic Remediationmentioning
confidence: 99%
“…In this table K = {products} n i / {reactants} n i where n i is the stoichiometric coefficient of compound i in the reaction and the braces show the activities. Table 1 Important chemical reactions of Hg 2+ with available ligands in the system and their stability constants [31][32][33]35,36] Reaction…”
Section: Approachmentioning
confidence: 99%